The Functioning of Parcha in Early 20th Century Tatar Literature as a Compositional and Architectonic Form of the whole - Amineva, Venera R. (The New Research of Tuva, 2025)
The article offers the first scholarly investigation into the functioning of parcha in early 20th century Tatar literature as both a compositional and architectonic form of the whole. This analysis refines and deepens our understanding of the developmental trajectories of the genre-style system in Tatar national literature. In a broad sense, parcha referred either to an excerpt from a larger work or to a miniature literary form. In the narrower sense, within the literature of this period parcha is presented specifically as a compositional and architectonic device. It is established that, as a compositional method, parcha generates a dynamic tension between openness and closure, completion and incompletion of the text. This activates the fragmentary logic traditionally associated with the "excerpt" genre in Russian and European literatures—one that emphasizes the inner boundlessness of the depicted world. Such patterns are evident in the poems of S. Ramiev and several miniatures by Dardmend. The artistic and aesthetic potential of parcha as a value-bearing architectonic structure of the depicted world becomes manifest in miniatures that trace their generic origins to the descriptive section of the qasida (wasf), with its contemplative and landscape-oriented content rooted in a harmonious worldview. Poems of this type are characterized by compositional closure and precision in syntactic, rhythmic, and strophic boundaries. This is exemplified in Dardmend’s poems, G. Tukay’s ideal landscapes, and portrayals of nature in the lyrics of Sh. Babich. The study identifies a core trend in the development of such miniatures, which preserve the “generic memory” of wasf: the gradual liberation from thematic, compositional, and stylistic conventions and the growing discovery of the immanent potential of their internal structure through interactions with other genres, non-generic forms, and types of discourse.